AUGMENTED REALITY (AR) KIDS DICTIONARY: FOR YOUNG CHILDREN EARLY LEARNING - Mohd Fauzi, Nur Fatin Firzanah (IRC, 2019)
Nowadays, kids are being exposed early with the advanced of technologies through smartphones, computers as well as tablets. This paper introduces a recently started research project that aims for the kids learning through online dictionary based on Augmented Reality through mobile application that will serve as an educational tool for the kids age 2 to 7 years old. The main focus of this document is a dictionary contains of three categories which are Animals, Fruits and Vehicles. AR Kids Dictionary will appear in 3D model with the interactivity of playing the object sound and object name in English. Five basic animals and occupation respectively which are common in the kid’s life will be available through this AR Kids Dictionary Apps. Through this application, parents can observe their kid’s growth and improve their recognition, vocabulary and reading skills. This application also serves as an entertainment to make learning a fun activity at early stage